The economy of India and a modern version from the present to the future - Fathullah Jasim Mustafa3, Fekri Ahmed Lahmood*1,; Khaleel Abd, Mustafa Ismaeel (Opción, 2019)
The present research paper aims mainly to study the issue ofglobalization from a present and future perspective. As a result, thepaper will focuses on practical study at India state regarding somemajor factors affecting positively or negatively on the overalleconomic due to the distribution of the globalization. Through thestudy, we found that the Indian government provided facilities forforeign companies to encourage the growing economy. Inconclusion, opportunities and challenges will emerge as a naturalconsequence of shifts in environments from the political, security,regional and global security perspectives